Participation in Students Industrial Work Experience Scheme and skills acquisition among Library and Information Science students in selected Universities in South-South, Nigeria - Inyang, Comfort Linus; Okwueze , Eucharia Amaka (Communicate: Journal of Library and Information Science, 2024)
The study investigated the relationship between participation in students industrial work experience scheme and skills acquisition among Library and information science students in selected Universities in South-South, Nigeria. To accomplish the research purpose, two research questions were formulated to guide the study. Literature was reviewed according to the variables of the study. The correlational survey research design was adopted for this study and the population of the study was 296 (two hundred and ninety six students). This was also used as sample. Students Industrial Work Experience Scheme Skill Acquisition Questionnaire (SIWESSAQ) was the main instrument used for data collection. The reliability index obtained for the instrument was established through Cronbach Alpha Reliability Co-efficient method. The data collected were analyzed using simple regression analysis at 0.05 level of significance. The result of the analysis showed that information consultancy and information repackaging significantly related with Students Industrial Work Experience Scheme. It was concluded that, skills acquisition among Library students significantly predict student’s industrial work experience. It was recommended among others that Students should take industrial training very seriously and ensure that they undergo the training in establishments where they stand to benefit from practical training.